Midwives' Support for Couples in Japanese Hospitals and Clinics During the COVID‐19 Pandemic: A Cross‐Sectional Survey - Kumiko Nakajima; Ayano Hirose; Megumi Yoshino; Maho Watanuki; Tomoko Nameda (Nursing Open)
ABSTRACT Aims Severe restrictions and changes in perinatal care, social isolation, and disruption of marital relationships due to the coronavirus disease COVID‐19 pandemic have become problematic. This study aimed to clarify the status of the health guidance and group education provided by midwives in Japanese hospitals and clinics before and after the COVID‐19 pandemic. Furthermore, this study clarifies the role of midwifery support in promoting marital relationships. Design Cross‐sectional questionnaire survey. Methods The STROBE statement was used to guide this study. Overall, 890 midwives working in hospitals and clinics throughout Japan were recruited for this study, which yielded 216 valid questionnaires. Results The COVID‐19 pandemic has transformed Japanese midwifery into a flexible system that can provide non‐face‐to‐face individualised support for couples. However, continuous midwifery care was not provided to couples prior to the COVID‐19 pandemic. As a result, midwifery support for couples has been limited since the outbreak of COVID‐19. During the COVID‐19 pandemic, there was a significant association between midwifery practice and the importance of promoting marital relationships. Conclusion The challenge in providing midwifery support to couples is providing individualised and ongoing support in combination with direct and indirect support.